2018
DOI: 10.1111/pde.13695
|View full text |Cite
|
Sign up to set email alerts
|

Infantile hemangiomas with minimal or arrested growth: A retrospective case series

Abstract: Background/objectives Infantile hemangiomas (IH) with minimal or arrested growth (MAG) constitute a distinctive subset of IH based on their clinical characteristics and natural history. They are often confused with capillary malformations. Methods A retrospective observational study has been carried out in which clinical and perinatal characteristics have been evaluated in all IH‐MAG evaluated in our Dermatology Department in a 5‐year period (January 2013‐December 2017). Results A total of 14 IH‐MAG affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
4
19
0
2
Order By: Relevance
“…Female dominance was somewhat lower than that for classic IHs, where the female: male patient ratio is 3.5:1. One previous study on IH-MAGs reported a sex ratio of 1.8:1, similar to our data; 2 However, another reported a ratio of 3.3:1 9 . In addition, it has been reported that IHs occur frequently in premature infants or those with LBW 8 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Female dominance was somewhat lower than that for classic IHs, where the female: male patient ratio is 3.5:1. One previous study on IH-MAGs reported a sex ratio of 1.8:1, similar to our data; 2 However, another reported a ratio of 3.3:1 9 . In addition, it has been reported that IHs occur frequently in premature infants or those with LBW 8 .…”
Section: Discussionsupporting
confidence: 91%
“…Although data for interpretation of this result is insufficient, it is possible to find more factors associated with the size difference through future study. Non-proliferative lesions were found more frequently on the lower body, similar to reports from other studies 2 9 . Although this study did not reveal a significant difference in the anatomical location of the lesions of total IH-MAGs, it is worth noting that there was a marked predominance of non-proliferative lesions on the lower body.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lesions we observed are not described in articles concerning cutaneous abnormalities 2 or vascular phenomenon of the newborn. [3][4][5] The bilateral character, absence of vasoconstrictive halo, non-congenital nature, and rapid resolution rule out alternative diagnoses such as infantile hemangiomas with minimal or arrested growth 6 or capillary malformations.…”
Section: Ta B L E 1 Characteristics Of 20 Cases Of Transient Abdominal Telangiectasia Of the Newbornmentioning
confidence: 99%